UZBEK PROVERBS AND EXPRESSION OF FOOD NAMES IN THEM (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This in the article Uzbek people proverbs and in them food of names expression was studied. Bread, milk, oil, grain products based on proverbs analysis done.